ANALISIS KESTABILAN LERENG BLOK BUKIT RAHMAT PT. CAHAYA BUMI PERDANA, KOTA SAWAHLUNTO - Muhammad Fadillah; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Cahaya Bumi Perdana is a company engaged in coal mining, located in Sawahlunto City, West Sumatra Province with an area of 103.10 Ha. There is a slope with a height of 23.2 meters, a slope of 78ο and this slope is 7 meters behind the BT 04 tunnel door. With these slope conditions, it has the potential to endanger workers and hinder production.The results of testing the physical and mechanical properties of the soil obtained the original bulk density value of 18.88 kN/m3 , cohesion (c) 8.6054 kN/m2 and inner shear angle (ϕ) 43,54ο . The results of the physical and mechanical properties of the sandstone are the original bulk density of 22.85 kN/m3 , the cohesion (c) of 184.3 kN/m2 and the inner shear angle (ϕ) 53,4894ο . The analysis and recommendations used the simplified bishop and simplified janbu methods. The results of the study are landslides in the form of landslides with a 40% possibility of landslides in the direction of landslides N 283ο E/78ο . Therefore, a single slope recommendation is carried out, so the slope is 71° and the safety factor (FK) is 1.333 and the slope is in a safe condition. Keywords: Physical and Mechanical Properties of Soil and Rocks, Slope Geometry, Simplified Bishop, Simplified Janbu, Safety Factors